(untitled) (Élisée - Revista de Geografia da UEG, 2015)
O artigo analisa o processo de formação da centralidade na Cidade de Goiás. A pesquisa faz um levantamento da centralidade e sua estruturação, buscando verificar como os agentes produtores do espaço urbano fomentaram e elegeram a Av. Dário de Paiva Sampaio como eixo do comércio local. A metodologia foi baseada em elaboração e aplicação de formulários e entrevistas, subsidiarias para compreender como ocorreu o processo de formação da centralidade do setor João Francisco além de mapear os equipamentos de comércios e serviços da Av. Dario de Paiva Sampaio. Palavras-chave: Espaço urbano. Setor João Francisco. Cidade de Goiás. Centralidade. The centrality of cidade de goiás (Goiás, Brazil): the setor João Francisco neighbourhood and the role of avenue Dário de Paiva Sampaio in the structuration of the urban space The article analyses the process of centrality’s formation in Cidade de Goiás, state of Goi-ás, Brazil. The research makes a gathering of the centrality and its structuration, searching the verifica-tion of how the urban space producers promoted and elected avenue Dário de Paiva Sampaio as center-line of the local businesses. Thus, the methodology basis itself in elaboration and application of forms, and interviews, were helpful to apprehend how the process of centrality’s formation of Setor João Fran-cisco neighborhood happened, further mapping the trade and services equipments of avenue Dário de Paiva Sampaio.Keywords: urban space. Setor João Francisco neighborhood. Cidade de Goiás. centrality.